(untitled) (The Research of Medical Science Review, 2025)
Objective: To assess the diagnostic performance of ultrasound (US) for detection of hepatocellular carcinoma (HCC) compared to histopathology as the gold standard. Methodology: It was a cross-sectional study carried out at Medcare International Hospital, Gujranwala, from July to December 2023. One hundred patients diagnosed with HCC were included; 90 patients were clinically suspected of having HCC and aged ≥ 18 years. Patients with previous treatment for liver cancer or incomplete diagnostic data were excluded. US was performed in all participants, followed by histopathological confirmation. The results are analyzed for the calculation of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy. Results: US correctly detected 62 cases of true positive (TP) and 18 cases of true negative (TN) HCC among the 90 patients. Five cases were FP and five were FN. The sensitivity, specificity, PPV, NPV, and total diagnostic accuracy were 92.5%, 78.2%, 92.1%, 78.3%, and 88.9%, respectively (p < 0.05). In conclusion, the study shows that US is a low-cost, highly sensitive, and diagnostic imaging modality with noninvasive characteristics for the diagnosis of HCC. This reinforces its importance as a screening tool, especially in resource-poor areas.